Analysis of the Financial Performance of Tasikmalaya City MSMEs through Financial digital literacy, Digital payment, and Financial report application in the Era of Digitalization of MSMEs - Oktaviani, Nita Fauziah; Yusnita, Rita Tri; Yuniar, Evilia Sri (Business Education Program of Universitas Pendidikan Indonesia, 2024)
The current phenomenon is that digitalization for some MSMEs provides benefits and benefits, but for several other MSMEs, especially with all their limitations, digitalization seems to bring serious challenges due to various factors. Therefore, various parties are trying to carry out activities to boost the capabilities of MSMEs in terms of digital financial literacy and digital payment skills, and financial reporting applications in order to improve their financial performance. The research method used a mixed method (mixed method) sequential explanatory on 40 MSMEs in Tasikmalaya City. The research results show that the financial performance of Tasikmalaya City MSMEs has an average Current Ratio of 3.9, Debt to Equity Ratio of 0.54 and Net Profit Margin of 1.38. In terms of financial digital literacy it is good, and for the use of digital payments it is good because on average MSMEs use more than one type of digital payment, and for financial reporting applications it was found that MSMEs on average use premium applications compared to free ones because the features are more complete and also the use of more than two financial reporting applications because each application has its own advantages and disadvantages. In addition, quantitatively shows that simultaneously digital financial literacy, digital payments and the application of financial reports have a significant influence on the financial performance of MSMEs and partially financial digital literacy and digital payments have a significant influence on the financial performance of MSMEs, while the application of financial reports has no influence. significant impact on the financial performance of MSMEs.